Exploring the Role of Multicultural Education in Promoting Social Harmony in Malaysia - Rusli Wan (Journal of Cultural Relativism (JCR), 2025)
Malaysia is widely recognized as a multicultural nation characterized by ethnic, religious, linguistic, and cultural diversity. While this diversity contributes significantly to national identity and social development, it also presents challenges related to social cohesion, intercultural understanding, and national unity. Multicultural education has emerged as an important educational approach for promoting social harmony by fostering respect, tolerance, and positive interactions among diverse communities. This study explores the role of multicultural education in promoting social harmony in Malaysia through a systematic literature review of contemporary research and policy documents. The findings indicate that multicultural education contributes to social harmony by enhancing intercultural competence, reducing prejudice, strengthening social cohesion, and encouraging inclusive participation in educational settings. Furthermore, multicultural educational practices facilitate mutual understanding and collaborative relationships among students from different cultural backgrounds. The study proposes a conceptual framework illustrating how multicultural education promotes social harmony through intercultural engagement and inclusive citizenship development. The findings provide valuable insights for educators, policymakers, and educational institutions seeking to strengthen national unity and social cohesion in increasingly diverse societies.